Quality indicator selection for the Canadian Partnership against Cancer rectal cancer project: A modified Delphi study. (20th March 2021) - Pooni, Amandeep; Schmocker, Selina; Brown, Carl; MacLean, Anthony; Hochman, David; Williams, Lara; Baxter, Nancy; Simunovic, Marko; Liberman, Sender; Drolet, Sébastien; Neumann, Katerina; Jhaveri, Kartik; et al.
Abstract: Aim: It is well established that (i) magnetic resonance imaging, (ii) multidisciplinary cancer conference (MCCs), (iii) preoperative radiotherapy, (iv) total mesorectal excision surgery and (v) pathological assessment as described by Quirke are key processes necessary for high quality, rectal cancer care. The objective was to select a set of multidisciplinary quality indicators to measure the uptake of these clinical processes in clinical practice. Method: A multidisciplinary panel was convened and a modified two‐phase Delphi method was used to select a set of quality indicators. Phase 1 included a literature review with written feedback from the panel. Phase 2 included an in‐person workshop with anonymous voting. The selection criteria for the indicators were strength of evidence, ease of capture and usability. Indicators for which ≥90% of the panel members voted 'to keep' were selected as the final set of indicators. Results: During phase 1, 68 potential indicators were generated from the literature and an additional four indicators were recommended by the panel. During phase 2, these 72 indicators were discussed; 48 indicators met the 90% inclusion threshold and included eight pathology, five radiology, 11 surgical, six radiation oncology and 18 MCC indicators. Conclusion: A modified Delphi method was used to select 48 multidisciplinary quality indicators to specifically measure the uptake of key processes necessary for high quality care of patients with rectal cancer. These quality indicators will be used in future work to identify and address gaps in care in the uptake of these clinical processes.